Inhaled Furan Selectively Damages Club Cells in Lungs of A/J Mice. (October 2019) - Tǎbǎran, Alexandru-Flaviu; O'Sullivan, M. Gerard; Seabloom, Donna E.; Vevang, Karin R.; Smith, William E.; Wiedmann, Timothy S.; Peterson, Lisa A.
Furan, a possible human carcinogen, is a product of incomplete combustion and is present in cigarette smoke, engine exhaust, and processed food. Oral administration induces liver toxicity and carcinogenesis in F344 rats and B6C3F1 mice. To assess possible adverse effects from inhalation, A/J mice were nose-only exposed for 3 hours to furan (0, 30, 75, 150, 300, or 600 ppmv) and euthanized after 24 hours, 48 hours, or 1 week. Histopathology evaluation revealed bronchiolar club cell necrosis (diffuse, marked) with airway denudation following exposure to 300 and 600 ppmv furan with evidence of club cell regeneration and partial repair after 1 week. Initial signs of hepatotoxicity were observed in the 150 ppmv furan-exposed group. Acute necrosis and mineralization were observed in livers at 24 and 48 hours with hepatocyte regeneration by 1-week postexposure in mice exposed to 300 and 600 ppmv furan; the 300 ppmv exposed group had multifocal mineralization that evoked a mild granulomatous response. Measurement of urinary furan metabolites confirmed that the mice metabolized furan to the toxic intermediate, cis -2-butene-1, 4-dial. These observations indicate that inhaled furan is toxic to lungs with club cells as the target as well as liver.